Cervical and Thoracic Spondylotic Myelopathies - Onofrei, Ligia V.; Henrie, A. Michael (Seminars in Neurology, 2021)
Spondylotic myelopathies are among the most common disorders of the spine, yet the clinical and treatment approach is far from standardized. This article discusses our current understanding of the epidemiology, pathophysiology, clinical assessment, natural history, and treatment options in degenerative myelopathies of the cervical and thoracic spine. We additionally review diagnostic modalities including imaging modalities of the spine and neurophysiological tools such as electromyography/nerve conduction studies, somatosensory-evoked potentials, and motor-evoked potentials. Assessment instruments that can be used for the assessment of myelopathies are reviewed, including the Japanese Orthopedic Association (JOA) score, modified-JOA scale, Nurick scale, nine-hole peg test, and 30-m walking test. We also review common disorders that mimic spondylotic myelopathies, as well as helpful diagnostic clues in differentiating spondylotic and nonspondylotic myelopathies.
Keywords: cervical myelopathy; thoracic myelopathy; degenerative myelopathies